Some early recollections of A.A. Bancroft by Azaria Ashley Bancroft (diary) - Azariah Ashley Bancroft:::::: (1880)
Diary consists of one letter-sized volume with a leather cover. Rare Books collection inventory number is M-223.In a prefatory note the author states, "This book should be considered the property of H.H. Bancroft, as he furnished the blank, and was writtten at his urgent request". This manuscript was used extensively in H.H. Bancroft's autobiography, "Literary industries". The book "The golden wedding" by A.A. Bancroft was actually written by H.H. Bancroft based on A.A. Bancroft's recollections.